Sanborn Harbor, Nagai Island, Alaska / drawn by H. Lindenkohl - Lindenkohl, H. (Henry) (U.S. Coast Survey, 1872)
Relief shown by hachures and spot heights. Depths shown by soundings. Includes notes. "No. 10" -- upper right margin. 1:40,000